Surveillance of Acute SARS-CoV-2 Infections in School Children and Point-Prevalence During a Time of High Community Transmission in Switzerland - Kriemler, Susi; Ulyte, Agne; Ammann, Priska; Peralta, Gabriela P.; Berger, Christoph; Puhan, Milo A.; Radtke, Thomas (Frontiers in Pediatrics, 2021)
Background: Switzerland had one of the highest incidence of SARS-CoV-2 infections in Europe during the second wave. Schools were open as in most of Europe with specific preventive measures in place. We aimed to pilot a surveillance system that detects acute SARS-CoV-2 infections in schools and possible transmission within classes. Methods: 14 out of the randomly selected sample of the Ciao Corona cohort study participated between December 1 and 11. We determined point-prevalence of acute SARS-CoV-2 infections of school children. A buccal swab for polymerase chain reaction (PCR) and a rapid diagnostic test (RDT) to detect SARS-CoV-2 were taken twice 1 week apart (T1 and T2). A questionnaire assessed symptoms compatible with a SARS-CoV-2 infection. Results: Out of 1299 invited children, 641 (49%) 6- to 16-year-old children and 66 teachers from 14 schools and 67 classes participated in at least 1 of 2 testings. None of the teachers but 1 child had a positive PCR at T1, corresponding to a point-prevalence in children of 0.2% (95% CI 0.0% to 1.1%). No positive PCR was detected at T2. The child with positive PCR at T1 was negative on the RDT at T1 and both tests were negative at T2. There were 7 (0.6%) false positive RDTs in children and 2 (1.7%) false positive RDTs in teachers at T1 or T2 among 5 schools (overall prevalence 0.7%). All 9 initially positive RDTs were negative in a new buccal sample taken 2 hours to 2 days later, also confirmed by PCR. 35% of children and 8% of teachers reported mild symptoms during the 5 days prior to testing. Conclusion: In a setting of high incidence of SARS-CoV-2 infections, unrecognized virus spread within schools was low. Schools appear to be safe with the protective measures in place. Specificity of the RDT was within the lower boundary of performance and needs further evaluation for its use in schools. Given the low point prevalence, a targeted test, track, isolate and quarantine (TTIQ) strategy for symptomatic children and school personnel adapted to school settings is likely more suitable approach than surveillance on entire classes and schools.